Ecological risk assessment in a tropical wetland contaminated with gasoline: Tier 1. Issue 5 (4th July 2017) - Mendes, Maíra P.; Salomão, André L. S.; Niemeyer, Júlia C.; Marques, Marcia
ABSTRACT: To assess natural attenuation and the efficiency of remediation actions after more than two years a large accident with gasoline spill contaminated a wetland in a tropical region, an Ecological Risk Assessment based on the Dutch Triad was applied. In total, eight surface water-sampling points were distributed randomly in the affected area and on reference area upstream the contaminated site, with similar ecological characteristics. Risks based on chemical, ecotoxicological, and ecological lines of evidence (LoE) were calculated to integrate the environmental risk indexes. The chemical risk was derived from toxic pressure coefficients based on the total BTEX and naphthalene concentrations. Ecotoxicological LoE based on acute toxicity with Daphnia similis and Aliivibrio fischeri bioassays and chronic toxicity with Desmodesmus subspicatus bioassay contributed to raise uncertainty due to low sensitivity of acute assays. Genotoxicity and endocrine disruption biomarkers of Oreochromis niloticus were used to calculate the Biomarker Stress Index (BSI) assumed as Ecological Risk Index. The integration of the Chemical Risk Index with BSI to estimate the Biological Vulnerability Index allowed a meaningful analysis of the threats to the aquatic ecosystem, thereby supporting managers and decision-makers.